Sulforaphane Delays Fibroblast Senescence by Curbing Cellular Glucose Uptake, Increased Glycolysis, and Oxidative Damage. (22nd November 2018) - Hariton, Florence; Xue, Mingzhan; Rabbani, Naila; Fowler, Mark; Thornalley, Paul J.
Abstract : Increased cell senescence contributes to the pathogenesis of aging and aging-related disease. Senescence of human fibroblasts in vitro may be delayed by culture in low glucose concentration. There is also accumulating evidence of senescence delay by exposure to dietary bioactive compounds that activate transcription factor Nrf2. The mechanism of cell senescence delay and connection between these responses is unknown. We describe herein that the cruciferous vegetable-derived metabolite, sulforaphane (SFN), activates Nrf2 and delays senescence of human MRC-5 and BJ fibroblasts in vitro . Cell senescence is associated with a progressive and marked increased rate of glucose metabolism through glycolysis. This increases mitochondrial dysfunction and overwhelms defences against reactive metabolites, leading to increasing proteomic and genomic oxidative damage. Increased glucose entry into glycolysis in fibroblast senescence is mainly mediated by increased hexokinase-2. SFN delayed senescence by decreasing glucose metabolism on the approach to senescence, exhibiting a caloric restriction mimetic-like activity and thereby decreased oxidative damage to cell protein and DNA. This was associated with increased expression of thioredoxin-interacting protein, curbing entry of glucose into cells; decreased hexokinase-2, curbing entry of glucose into cellular metabolism; decreased 6-phosphofructo-2-kinase, downregulating formation of allosteric enhancer of glycolysis fructose-2, 6-bisphosphate; and increased glucose-6-phosphate dehydrogenase, downregulating carbohydrate response element- (ChRE-) mediated transcriptional enhancement of glycolysis by Mondo/Mlx. SFN also enhanced clearance of proteins cross-linked by transglutaminase which otherwise increased in senescence. This suggests that screening of compounds to counter senescence-associated glycolytic overload may be an effective strategy to identify compounds with antisenescence activity and health beneficial effects of SFN in longevity may involve delay of senescence through glucose and glycolytic restriction response.